ANALISIS TINGKAT PELAYANAN JALAN AKIBAT AKTIVITAS PASAR TRADISIONAL KOTO BARU KABUPATEN TANAH DATAR - Helga Yermadona (Ensiklopedia of Journal, 2019)
On every Monday there is a traffic jam on the Padang Panjang-Bukittinggi road due to the activities of the Koto Baru traditional market in Tanah Datar. Transactions of vegetable traders on the shoulder of the road, makes vehicle speed becomes low. The purpose of the study was to determine the level of services due to market activities and to find solutions to the traffic jam. This research uses survey method to obtain primary data on traffic volume and side friction, then analyzed using PKJI, secondary data in the form of the population, and comparing the effect of the application of on-street parking and off street parking. The results showed that the traffic volume at peak hours at 14.00-15.00 was 1994 upc/hr. DS value> 0,75 indicates a problem with the road due to traditional market activities. Analysis of scenario 1 with the application of on-street parking is obtained by DS 0,72 and scenario 2 with off street parking value DS becomes 0,68. Scenario 2 was chosen as an alternative traffic jam solution for the Koto Baru Market, because produced a smaller DS than scenario 1. Keywords: level of service, traditional market, traffic jam, and PKJI.